The Influence of Non-Interest Income on the Profitability of Conventional Banks Listed on the Indonesia Stock Exchange - Renaldy Alam Pratama; Alifia Nova Azzahra; Susy Muchtar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the factors that influence the profitability of conventional banks in Indonesia with Return on Assets (ROA) as the main measure. This study uses a quantitative method with panel data regression to examine the effect of Non-Interest Income (NII), bank size, Loan Loss Provision (LLP), Capital Adequacy Ratio (CAR), and overhead costs on the profitability of conventional banks listed on the Indonesia Stock Exchange (IDX) in the period 2019–2024. Data were obtained from annual financial reports and other secondary sources such as IDX, Bank Indonesia, and the World Bank. The results showed that NII did not have a significant effect on profitability, indicating that conventional banks still rely on interest income as the main source of profit. Bank size has a positive effect on ROA, with larger banks benefiting from economies of scale and operational efficiency. LLP has a negative effect on profitability, indicating that increasing loan loss provisions reduce bank profits. CAR has a positive effect, indicating that strong capitalization increases investor confidence and financial stability. Meanwhile, overhead costs have a negative effect on ROA, emphasizing the importance of operational efficiency in increasing profitability. This study recommends further research considering Islamic banks and macroeconomic factors for a more comprehensive understanding of banking profitability in Indonesia.